The neuroendocrine stress-response in insects: the history of the development of the concept - M. A. Eremina; N. E. Gruntenko (Вавиловский журнал генетики и селекции)
The neuroendocrine stress-response is an effective defense mechanism against adverse influences of various nature. This reaction is universal and appears in response to stimuli that are unusual not just for living and habitat of the species, but also for each population. Here we review a progressive change of theoretical concepts, approaches and methods of research in this scientific field: beginning with the development of the stress concept by H. Selye and up to the present day. In 1982 H. Selye defined stress as a combination of stereotypical phylogenetic programmed  reactions of the organism that are caused by any strong, superstrong or extreme influences and are followed by a reorganization of the organism’s adaptive forces. The stress-causing agent was named a stressor. In the dy namics of the complex of nonspecific protectiveadaptive reactions that respond to a stressful influence aimed at cultivating the organism’s resistance to any factor, it is possible to logically identify three stages (“the Selye triad”): 1) alarm state, 2) resistance state, 3) exhaustion state. The duration and the expression of each stage can vary depending on the nature and strength of the stressor agent, the species of the animal and the physiological state of the organism. The lack of a hypothalamic-pituitary-adrenocortical system in insects was considered a proof of their inability to develop a stress reaction of the warm-blooded animals’ type. Nevertheless, since the early 1980s, enough evidence of the development of stress reaction in insects has been gathered, which emphasizes the conservative nature of the stress reaction in mammals and insects. The similarity in the neurochemical and physiological changes in invertebrates and vertebrates in response to a stressful influence indicates that the response to a stressor is a complex of ancient mechanisms preserved in evolution. Insects present unique opportunities for experimentation, which can allow us to understand the basic mechanisms of stress reactions. In insect larvae the mechanism of stress reaction has been studied in detail. In this century, the main efforts of researchers are aimed at studying the mechanisms of stress reaction in imago and genetic control of its individual links. The study of stress reaction in insects has both theoretical importance, as it demonstrates the convergence of evolutionary pathways of adaptive transformations in such distant taxa as insects and mammals, and practical importance, since the patterns of this reaction’s mechanisms can be used in modeling hereditary or acquired human diseases, in developing breeding methods for economically valuable insects and in finding ways to fight insect pests